Risk Factors for the Completion of the Cold Loop Hysteroscopic Myomectomy in a One-Step Procedure: A Post Hoc Analysis. (20th May 2018) - Mazzon, Ivan; Favilli, Alessandro; Grasso, Mario; Horvath, Stefano; Bini, Vittorio; Di Renzo, Gian Carlo; Gerli, Sandro
Abstract : Introduction. The aim of the study was to analyze which variables influenced the completion of a cold loop hysteroscopic myomectomy in a one-step procedure in a large cohort of patients. Materials and Methods. A retrospective cohort study of 1434 cold loop resectoscopic myomectomies consecutively performed. The study population was divided into two groups according to the number of procedures needed to accomplish the treatment. Variables influencing the completion of hysteroscopic myomectomy in a one-step procedure were investigated. Results. A total of 1434 resections were performed and 1690 myomas in total were removed. The procedure was accomplished in a one-step procedure in 1017 patients (83.7%), whereas 198 women (16.3%) needed a multiple-step procedure. The multivariate analysis showed that the size, the number of myomas, and the age of patients were significantly correlated with the risk of a multiple-step procedure. No correlation was revealed with the grading of myomas, parity, and the use of presurgical GnRH-agonist therapy. Conclusions. In case of multiple fibroids, the intramural development of submucous myomas did not influence the completion of cold loop hysteroscopic myomectomy in a one-step procedure. The size of myomas and the age of patients were significantly correlated with the need to complete the myomectomy in a multiple-step procedure.